Learning Motivation According to Cognitive Style (meditation-impulsiveness) and its relationship with performing some Skills in Artistic Skills in Gymnastics for Men - Humam Abass Sayhood; Suzan Saleem Dawood (College of Physical Education and Sport Sciences, 2021)
The research aimed at identifying the relationship between learning motivation according to cognitive style (meditation - impulsiveness) on skill performance in artistic gymnastics for men.  The subjects were (240) second-year college of physical education and sport sciences college students for the academic year (2020 - 2021). Twenty students were selected for the pilot study, (90) students were divided into two groups (50) meditation and (40) impulsiveness a questionnaire was applied followed by artistic performance tests on three apparatuses; floor, vault, and rings. The results showed a significant correlation between learning motivation and learning artistic skills in men's gymnastics for the impulsiveness group. In addition to that, the results showed a significant correlation between learning motivation and learning artistic skills in men's gymnastics for the meditation group as well as no sign was found on the rings.